Dynamic strength and failure modes of sandstone under biaxial compression. (April 2020) - Liu, K.; Zhao, J.; Wu, G.; Maksimenko, A.; Haque, A.; Zhang, Q.B.
Abstract: Geomaterials are increasingly being subjected to the quasi-static confinements and dynamic loadings, and thus it is critical to characterise dynamic behaviour under the coupled static-dynamic loading conditions. In this study, a series of dynamic biaxial compression tests was performed on cubic specimens of sandstone by using a triaxial Hopkinson bar system, high-speed three-dimensional digital image correlation (3D-DIC) and synchrotron-based micro-computed-tomography (μCT). This testing apparatus allows for determining dynamic stress-strain behaviour of the specimen under biaxial static pre-stress ( σ 1, σ 2 ) conditions and different impact velocities (i.e. 15, 20 and 26 m/s), corresponding to average axial strain rates of 80, 200 and 250 s −1 . Both σ 1 and σ 2 applied in the tests varied from 0 to 40 MPa with an interval of 10 MPa. Dynamic strength and fracture behaviours of biaxially confined rocks were systematically characterised from macroscopic to microscopic, surface to interior and 2D to 3D by using the 3D-DIC and synchrotron-based μCT techniques. Experimental results show that, under the same biaxial pre-stresses, dynamic biaxial compressive strength of sandstone increases with strain rate, i.e. rate dependence. At a given impact velocity, dynamic biaxial compressive strength decreases with increasing pre-stress values ( σ 1 ) along the impact direction, while it enhances with the increase of intermediate principal stress ( σ 2 ) in the lateral direction, which is so-called confinement dependence. Besides, two types of dynamic stress-strain curves of rocks are observed under biaxial compression, which is associated with post-peak fracturing characteristics. High-speed 3D-DIC shows that rock fragments are ejected out of the free surface ( σ 3  = 0) with certain velocities including the translation and rotation, which resembles the rock ejection observed during drilling and blasting and even strong rockbursts. μCT reveals that the double "V" shapes of shear fractured zones are symmetrically generated under biaxial compression. The crack surface area, volume and dynamic fracture energy are also estimated under different confinements to characterise the damage of impacted rock. Graphical abstract: Image 1 Highlights: Biaxial static-dynamic coupled tests were conducted using a triaxial Hopkinson bar. The effects of strain rate and confinement on stress-strain curves and failure modes. Ejection velocity, displacement field and kinetic energy are measured by 3D-DIC. Micro-cracks of impacted specimens are identified by the synchrotron-based μCT. Fracture energy is calculated with the combination of high-speed 3D-DIC and μCT.